CORRELATION BETWEEN THE SEVERITY LEVEL OF MALOCCLUSION AND ORAL HYGIENE STATUS IN STUDENTS AT SMPN 1 MARABAHAN - Dilla Mayarani; Diana Wibowo; Aulia Azizah (Universitas Lambung Mangkurat, 2023)
ABSTRACTBackground: Malocclusion can affect oral hygiene through several circumstances, one of which is the attachment of debris and calculus due to difficulties in tooth brushing. Debris will be inaccessible and attached to the interdental part of the teeth which causes the accumulation of plaque as well as calculus. Purpose: The purpose of this research was to analyze about correlation between the severity level of malocclusion with the OHI-S status in students at SMPN 1 Marabahan. Material and Methods: This research is an observational analytic study using cross sectional approach. The sample size in this research was 46 samples of SMPN 1 Marabahan student. Data collection was performed using IOTN-DHC and OHI-S. Data analysis consisted of univariate analysis which described the character from each variable and bivariate analysis which connected two variables with spearman test. Results: The severity level of malocclusion at SMPN 1 Marabahan based on the highest IOTN-DHC was in the great need for orthodontic treatment category comprising of 19 respondents (41.30%). The oral hygiene status based on the highest OHI-S was in the category of poor with a total of 24 respondents (52.17%). Conclusion: There is a correlation between the severity level of malocclusion and oral hygiene. Higher severity level of malocclusion will affect oral hygiene status.Keywords: Adolescent, IOTN-DHC, Malocclusion, OHI-S, Oral hygiene.